A Critical Assessment of the Role of the Venice Commission in Processes of Domestic Constitutional Reform. (1st October 2015) - Visser, Maartje De
Abstract: Since its inception in 1990, the services of the European Commission for Democracy Through Law—more commonly known as the Venice Commission—to advise and assist on constitutional reform projects have been engaged with a growing frequency, by both European and non-European states. This development means that the Venice Commission is rapidly becoming an actor of significance in constitutional engineering and, further, that its involvement in processes of constitutional change across different jurisdictions may generate convergence in national constitutional designs and approaches. This Article offers an analysis of the Venice Commission's performance of this role, using its recent participation in constitutional reform projects in Iceland, Tunisia, Belgium, and Hungary as case studies. More particularly, it questions whether the current approach of the Venice Commission—characterized by virtually unbridled flexibility and pragmatism—is still appropriate given its evolution into an internationally recognized, independent authority on constitutional matters. The Article argues that safeguarding, and ideally enhancing, the quality and acceptability of the opinions prepared by the Venice Commission for the benefit of national constitution makers calls for a more elaborate set of procedural rules governing its working methods and a greater degree of sophistication in identifying the shared constitutional standards used to evaluate constitutional changes contemplated by its member states. The Commission should further be more attentive to the implications of having a growing number of non-European states among its members and take measures to ensure that all its members are treated in a consistent fashion and with due regard for their equality in status as democratic nations.